Navigating Jurisdictional Complexities in Cross-Border Disputes: A Review of the Areas of the Private International Law in Pakistan - Munir, Yasir (Tribhuvan University Law Journal, 2025)
This paper is a research on jurisdictional issues in international conflict in Pakistani private international law. It begins with an explanation of jurisdiction and an insistence on the fact that it is not a clear-cut concept, and may be defined in many ways depending on the context of the legal system under consideration. Globalization serves to strengthen cross-border interactions, but the complicated nature of differences in legal frameworks and etiquette poses severe challenges to Pakistan to amicably settle these agreements. The research evaluates the way, jurisdiction, choice of law, recognition, and enforcement of decisions, the four principal issues of PIL overcome these difficulties. It ascertains the special issues arising from overlapping jurisdictions, influences of international conventions, and the real issues in the method of enforcement of awards and judgments in Pakistan where the civil code is blended with the Sharia law. The effects of historical, legal, and cultural considerations that underpin jurisdictional issues in Pakistan are also brought out where and when required particularly because of the strategic location. Furthermore, it aims to offer the prescription for the enhancement of legal systems in Pakistan and offer different perspectives of different policies to achieve justice, equity, and fairness in international relations conflict. To address issues of jurisdiction and in the long run foster cross-border business and relations the paper seeks to advocate for judicial cooperation, and adherence to international norms and outline ways of ADR. This study is relevant to those in the capacity of academics or practitioners or involved in legislative processes focusing on international legal relations and conflict settlement in the contemporary legal framework.